2014
DOI: 10.1016/j.drudis.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis, platelets, microparticles and PAH: more than a clot

Abstract: Pulmonary arterial hypertension (PAH) is a progressive disease that involves pathological remodeling, vasoconstriction, and thrombosis. Alterations in hemostasis, coagulation, and platelet activation are consistently observed in PAH patients. Microparticles derived from platelets, inflammatory cells, and the endothelium are an increasingly well-recognized signal in a variety of cardiovascular diseases, including PAH. This review will focus on the role of coagulation, thrombosis, platelet activation, and microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 77 publications
2
43
0
2
Order By: Relevance
“…Our preliminary studies demonstrated that induction of mitophagy by CCCP significantly reduced platelet aggregation (DMSO = 27.8 ± 12.4%, n = 4 and CCCP = 5.1 ± 0.9%, n = 4, P = 0.01) consistent with mitophagy being protective against mitochondrial (dysfunction and damage)‐induced increased platelet activation (thrombosis) (Tang et al , ; ). Removing the dysfunctional mitochondria prevents increased activation and apoptosis, both of which induce thrombosis (Sinauridze et al , ; Lannan et al , ). The study of mitophagy knockout mice was now needed.…”
Section: Resultsmentioning
confidence: 99%
“…Our preliminary studies demonstrated that induction of mitophagy by CCCP significantly reduced platelet aggregation (DMSO = 27.8 ± 12.4%, n = 4 and CCCP = 5.1 ± 0.9%, n = 4, P = 0.01) consistent with mitophagy being protective against mitochondrial (dysfunction and damage)‐induced increased platelet activation (thrombosis) (Tang et al , ; ). Removing the dysfunctional mitochondria prevents increased activation and apoptosis, both of which induce thrombosis (Sinauridze et al , ; Lannan et al , ). The study of mitophagy knockout mice was now needed.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the study by Kornek et al., only 2 of 56 participants were classified as having F3/F4 fibrosis, making it difficult to examine any relationship between CD14 and F3/F4 fibrosis, which is important because F3/F4 fibrosis predicts liver‐related outcomes. 1,7 EVs have been shown to play a role in thrombosis, and are sensitive to isolation conditions . Our study isolated platelet poor plasma in citrate tubes as suggested best practice according to ISTH guidelines .…”
Section: Discussionmentioning
confidence: 99%
“…play a role in thrombosis, and are sensitive to isolation conditions. [18][19][20][21] Our study isolated platelet poor plasma in citrate tubes as suggested best practice according to ISTH guidelines. 22 EV counts and phenotypes may have differed between both studies, due to Kornek et al…”
Section: Discussionmentioning
confidence: 99%
“…Se ha identificado que tanto las MPs como los exosomas cumplen diferentes funciones fisiológicas que varían según la célula de origen, tales como hemostasia, angiogénesis, regulación inmune, migración celular, diferenciación celular, entre otros; donde su aumento excesivo se ha asociado en la patogénesis de diferentes patologías cardiovasculares, tumores, neurodegeneración y enfermedades autoinmunes, entre otras 44,45 . En relación a las ECV, varios grupos de investigación han propuesto que la participación deletérea de las MP y exosomas se relacionarían principalmente con su alto potencial proinflamatorio, prooxidatidante y protrombótico [46][47][48] . Estudios in vitro, muestran a estas microvesículas como mediadores proinflamatorios y que por sí solas tienen la capacidad de aumentar la sensibilidad de diversas células a nuevos estímulos, por medio de la transferencia intercelular de receptores de quimioquinas 49 , inducir la expresión de moléculas de adhesión y la producción de IL6, IL1β y proteína quimiotáctica de monocitos 1 (MCP-1) en células endoteliales, favoreciendo el rodamiento (rolling) de leucocitos y el contacto célula-célula 50 , transfiriendo también ácido araquidónico a leucocitos y células endoteliales 51 , y activando la vía clásica del complemento 52 .…”
Section: Micropartículas Y Exososomas Derivadas De Gr Su Relación Counclassified